Combustion of hazelnut shell-lignite blends in poly-particulate beds - Yilgin, Melek; Yildirim, Seda; Pehlivan, Dursun (Springer Heidelberg, 2023)
In this study, combustion behaviours of blends prepared from 2.18 mm mean size lignite and hazelnut shell particles in specific proportions were investigated using a vertical pre-heated furnace system through which air was flowing upwards by natural convection. The results revealed that the ignition time of the blends approached those of hazelnut shell with temperature and showed certain interactions of the two materials during the volatiles combustion period. Combustion time generally complied with volatiles and carbon combustion rates of the two materials and their blends. Carbon combustion time decreased with temperature and hazelnut ratio, and implied some interactions of the materials. Although any effect of initial furnace temperature and hazelnut ratio of the blends on the NOx emissions was not clearly seen, SO2 emission levels depended on these factors.
Keywords: Hazelnut shell; Lignite; Co-combustion; SO2 and NOx emissions